Effect of Mouthrinse Containing Propolis on Oral Microorganisms and Human Gingival Fibroblasts - Özan, Fatih; Sümer, Zeynep; Polat, Zübeyde Akın; Er, Kürşat; Özan, Ülkü; Değer, Orhan (European Journal of Dentistry, 2013)
Objectives: The aim of this study was to compare the effects of four different mouthrinse containing propolis solutions and mouthrinse containing 0.2% chlorhexidine (CHX) on oral microorganisms and human gingival fibroblasts.Methods: Four different solutions of propolis were prepared and propylene glycol and alcohol were used as solvents for each propolis sample. Mouthrinse containing propolis was prepared at four different concentrations as 10%, 5%, 2.5% and 1%. Besides, CHX was used as control group. The antibacterial effects of five solutions on oral microorganisms were tested and their cytotoxic effects on human gingival fibroblasts were evaluated by agar diffusion test.Results: At this concentrations effectiveness of mouthrinse containing propolis samples on oral microorganisms were not found as effective as CHX. On the contrary, samples found less cytotoxic on human gingival fibroblasts than CHX.Conclusions: Standardized preparations of propolis can be used as a mouthrinse at appropriate concentrations. To obtain a standardized chemical composition, advanced researches are needed. (Eur J Dent 2007;1:195-201)
Keywords: Mouthrinse; Propolis; Chlorhexidine; Antibacterial activity; Cell culture